Odpowiedzi

2010-02-17T19:14:12+01:00
A). (-4)+(-4)x(-2)-(-12)=

-4 +8+12 = 16
b). [8-8x(-4)-12x(-3)]x(-2)=
[8+32+36]*(-2) = -152


c). (-34)+(-6)x[2-(-3)x4]=
-34 -6*(14) = -34 - 84= -118

d). {4-[-(-6)x(-3)+3]-13}x(-4)=

{4+15-13}x(-4) = -24
15 4 15
Najlepsza Odpowiedź!
2010-02-17T19:18:12+01:00
A). (-4)+(-4)x(-2)-(-12)=-8*10=80
b). [8-8x(-4)-12x(-3)]x(-2)=
[8+32+36]x(-2)=
-16-64-72=-152
c). (-34)+(-6)x[2-(-3)x4]=
-40x20=-800
d). {4-[-(-6)x(-3)+3]-13}x(-4)={4-[-18+3]-13}x(-4)={4+15-13}x(-4)=
6*(-4)=-24
21 2 21